2009
DOI: 10.1097/brs.0b013e31819e2b16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selective Anterior Versus Posterior Screw Instrumentation in Lenke5C Adolescent Idiopathic Scoliosis

Abstract: Selective anterior and posterior screw instrumentation both achieved good surgical lumbar and subsequent spontaneous thoracic correction. There was no statistically significant difference between the 2 groups in lumbar correction or thoracic correction, but fusion levels were shorter in the anterior group. Patients with late thoracic curve decompensation had smaller thoracolumbar/lumbar-thoracic Cobb ratios and less preoperative flexibility than those who did not decompensate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 15 publications
0
46
0
8
Order By: Relevance
“…Selective fusion has gained popularity over decades. 2,3,57 Although both anterior and posterior selective TL/L fusion turned out to be effective treatments for AIS with structural TL/L curve and compensatory thoracic curve, 3,8–15 studies have figured out that the anterior method may result in a higher incidence of kyphosis, pseudarthrosis, and loss of correction. 16 Posterior selective TL/L fusion has many advantages like better curve correction, less loss of correction overtime, less loss of blood, and shorter hospital stays over anterior approach, 12 and it has been widely accepted by spine surgeons in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Selective fusion has gained popularity over decades. 2,3,57 Although both anterior and posterior selective TL/L fusion turned out to be effective treatments for AIS with structural TL/L curve and compensatory thoracic curve, 3,8–15 studies have figured out that the anterior method may result in a higher incidence of kyphosis, pseudarthrosis, and loss of correction. 16 Posterior selective TL/L fusion has many advantages like better curve correction, less loss of correction overtime, less loss of blood, and shorter hospital stays over anterior approach, 12 and it has been widely accepted by spine surgeons in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the outcomes of patients with thoracolumbar and lumbar AIS treated with pedicle screw constructs; 8,10,[17][18][19]22,25 however, most of these studies reported only 2 years of follow-up. To the best of our knowledge, ours is the first such study to analyze the clinical and radiographic findings of posterior pedicle screw constructs at 5 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…22 Several studies that compared anterior spinal fusion with pedicle screw fixation for the treatment of thoracolumbar and lumbar AIS reported no statistically significant difference in coronal or sagittal curve correction between the 2 methods at 2 years after surgery. 10,19,25 However, in 2009, Geck et al compared patients with Lenke 5C AIS treated with a posterior release and pedicle screws with those who received anterior instrumentation; they found that at 2 years after surgery, the patients with pedicle screws had statistically significantly better curve corrections, better maintenance of corrections over time, and shorter hospital stays. 8 Although the long-term results for anterior constructs have been reported, clinical and radiographic outcomes of pedicle screw constructs are largely based on short-term follow-up.…”
mentioning
confidence: 99%
“…A spontaneous thoracic correction of 36% was shown in this study. Li et al [63] followed patients after selective lumbar fusion in Lenke 5C curves. They found an average of 57% lumbar curve correction and 26% thoracic curve correction with a minimum 2 year follow-up.…”
Section: Selective Thoracolumbar/lumbar Fusionmentioning
confidence: 99%